The Thymus in Chagas Disease: Molecular Interactions Involved in Abnormal T-Cell Migration and Differentiation - Pérez, Ana Rosa; de Meis, Juliana; Rodriguez-Galan, Maria Cecilia; Savino, Wilson (Frontiers in Immunology, 2020)
Chagas disease, caused by the protozoan parasite T. cruzi, is a prevalent parasitic disease in Latin America. Presently, it is spreading around the world by human migration, thus representing a new global health issue. Chronically infected individuals reveal a dissimilar disease progression: while nearly 60% remain without apparent disease for life, 30% develop life-threatening pathologies, such as chronic chagasic cardiomyopathy (CCC) or megaviscerae. Inflammation driven by parasite persistence seems to be involved the pathophysiology of disease. However, there is also evidence of the occurrence of autoimmune events, mainly caused by molecular mimicry and bystander activation. In experimental models of disease, is well established that T. cruzi infects the thymus and cause locally profound structural and functional alterations. The hallmark is a massive loss of CD4+CD8+ double positive (DP) thymocytes, mainly triggered by increased levels of glucocorticoids, although other mechanisms seem to act simultaneously. Thymic epithelial cells (TEC) exhibited an increase in extracellular matrix deposition, which are related with thymocyte migratory alterations. Moreover, medullary TEC showed a decrease expression of AIRE and altered expression of microRNAs, which might be linked to disrupting the normal negative selection of the T-cell repertoire. In addition, almost all stages of thymocyte development are altered, including an abnormal output of CD4-CD8- double negative (DN) and CD4+CD8+ double positive (DP) immature and mature cells, many of them carrying prohibited TCR-Vβ segments. Evidence has shown that DN and DP cells with an activated phenotype can be tracked in blood of humans with chronic Chagas disease and also in the secondary lymphoid organs and heart of infected mice, raising new questions about the relevance of these populations in the pathogenesis of Chagas disease and their possible link with thymic alterations and an inmunoendocrine imbalance. Here, we discuss diverse molecular mechanisms underlying thymic abnormalities occurring during T. cruzi infection and their link with CCC, which may contribute to the design of innovative strategies to control Chagas disease pathology.